USING CT AND MRI FOR IDENTIFICATION OF ARTERIAL HYPERENHANCEMENT IN PATIENTS WITH HEPATOCELLULAR CARCINOMA (World Bulletin of Public Health, 2023)
Given the varied prevalence and clinical settings, there has been some heterogeneity in the clinical guidelines regarding the method of imaging diagnosis for hepatocellular carcinoma (HCC). However, all methods used to diagnose HCC are based on the imaging diagnostic hallmarks of arterial enhancement and portal-delayed washout, as key alterations during hepatocarcinogenesis include elevated arterial flow and reduced portal venous flow. Arterial phase hyperenhancement is defined as enhancement in the arterial phase that is unequivocally greater than that of the surrounding liver according to the current major guidelines. Therefore, the objectives of our study were to compare the identification of hyperenhancement according to various phases on CT and MRI in patients with surgically proven HCCs as a reference standard using qualitative and quantitative imaging analyses.
Keywords: MRI; CT; Hepatocellular carcinoma